Growth reduction after defoliation is independent of CO2 supply in deciduous and evergreen young oaks. Issue 4 (27th February 2017) - Schmid, Sandra; Palacio, Sara; Hoch, Günter
Summary: Reduced productivity of trees after defoliation might be caused by limited carbon (C) availability. We investigated the combined effect of different atmospheric CO2 concentrations (160, 280 and 560 ppm) and early season defoliation on the growth and C reserves (nonstructural carbohydrates (NSC)) of saplings of two oak species with different leaf habits (deciduous Quercus petraea and evergreen Quercus ilex ). In both species, higher CO2 supply significantly enhanced growth. Defoliation had a strong negative impact on growth (stronger for Q. ilex ), but the relative reduction of growth caused by defoliation within each CO2 treatment was very similar across all three CO2 concentrations. Low CO2 and defoliation led to decreased NSC tissue concentrations mainly in the middle of the growing season in Q. ilex, but not in Q. petraea . However, also in Q. ilex, NSC increased in woody tissues in defoliated and low‐CO2 saplings towards the end of the growing season. Although the saplings were C limited under these specific experimental conditions, growth reduction after defoliation was not directly caused by C limitation. Rather, growth of trees followed a strong allometric relationship between total leaf area and conductive woody tissue, which did not change across species, CO2 concentrations and defoliation treatments.